Penatalaksanaan patah jarum akibat anastesi lokal pada ekstraksi gigi Management of broken needle cause by local anesthesia on teeth extraction - Saifuddin Kusuma N; Fonny Dahong; Muh. Ruslin (DiscoverSys Inc., 2012)
Since the inroduction of disposable needles, breakage of needles within tissues have become extremely rare.However, reports of needle breakage still appear. This paper discussed the cause of needle breakage, problem ofneedle breakage, prevention of needle breakage, and management of needle breakage. If the needle broken duringanesthesia of the alveolar dental nerve process, the needle will probably be located in the pterygomandibular space.It can migrate to vital structure.